2021
DOI: 10.1186/s12864-021-07711-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cis-regulatory motifs in first introns and the prediction of intron-mediated enhancement of gene expression in Arabidopsis thaliana

Abstract: Background Intron mediated enhancement (IME) is the potential of introns to enhance the expression of its respective gene. This essential function of introns has been observed in a wide range of species, including fungi, plants, and animals. However, the mechanisms underlying the enhancement are as of yet poorly understood. The goal of this study was to identify potential IME-related sequence motifs and genomic features in first introns of genes in Arabidopsis thaliana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…In the aforementioned study of Back and Walther (8) that used Arabidopsis thaliana as the model genome, a high positive correlation was estimated between the sequence variation in the first exons and gene expression, which would explain higher genomic variability of the first exon observed in our study. Also, in a slightly different context of across-species comparison based on the reference genome sequence, Castle (4) observed higher variability of coding regions in the proximity of the start and stop codons, so the ones typically corresponding to the first and the last exons, that is in line with our observation of SNP excess in the first and the last exons.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In the aforementioned study of Back and Walther (8) that used Arabidopsis thaliana as the model genome, a high positive correlation was estimated between the sequence variation in the first exons and gene expression, which would explain higher genomic variability of the first exon observed in our study. Also, in a slightly different context of across-species comparison based on the reference genome sequence, Castle (4) observed higher variability of coding regions in the proximity of the start and stop codons, so the ones typically corresponding to the first and the last exons, that is in line with our observation of SNP excess in the first and the last exons.…”
Section: Discussionmentioning
confidence: 57%
“…These specific roles may explain why the human DNA’s first intronic sequence is considered the longest and highly dense of regulatory chromatin marks (24, 25) Considering the criterion of SNP density, the above-mentioned studies identified the first introns as the most conserved regions, that however, provided a highly non-uniform distribution of SNPs along the intronic sequence (26) does not directly translate to the total low number of SNPs. Interestingly, in Arabidopsis thaliana , Back and Walther (8) observed that the first introns harbour more SNPs than the subsequent introns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40–50‐fold slower and the IPG is about one third of that of Ohadii , isolated from the harsh desert crusts environment, where the limited daily time interval enabling photoautotrophic activity favors fast growth. This is consistent with the suggestion that the presence of introns accelerates the expression of genes without serving as a binding site for transcription regulators, a phenomenon termed ‘intron‐mediated enhancement’ (Shaul, 2017; Lasin et al ., 2020; Back & Walther, 2021; and references therein). Furthermore, a recent study showed that in addition to the first intron, those located downstream also affect the expression of rbcS (the nuclear gene encoding the small subunit of RuBisCO) in C. reinhardtii (Baier et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the first intron of maize ubiquitin 1 ( ZmUbi1 ) located in the 5′-UTR region combines with CaMV 35S promoter leads to a over 90-fold increasement of gene expression in maize and bluegrass ( Vain et al, 1996 ). Many works have attempted to identify the key cis-elements in this process, but the detailed mechanism is still not clear, since it has been found that the sequence and splicing process are not the key feathers of these introns ( Rose and Beliakoff, 2000 ; Rose, 2004 ; Back and Walther, 2021 ). Thus, it’s promising to engineer these introns to enhance the strength of the promoters that drive the expression of the CRISPR/Cas9 system.…”
Section: Introductionmentioning
confidence: 99%